Affect regulation and pain in borderline personality disorder: a possible link to the understanding of self-injury - Niedtfeld, Inga; Schulze, Lars; Kirsch, Peter; Herpertz, Sabine; Bohus, Martin; Schmahl, Christian (Biological psychiatry, 2010)
Background - Patients with borderline personality disorder (BPD) experience intense emotions and often show a deficiency of emotion regulation skills. Moreover, they display high prevalence rates of self-injurious behavior. Patients report engaging in self-injurious behavior due to its immediate relief effects of emotional tension. Pain in BPD has further been observed to lead to a reduction in neural activity in the amygdala and anterior cingulate cortex, which may be attributed to patients' perception of relaxation. - Methods - To investigate the potential role of self-inflicted pain as a means of affect regulation in patients with BPD, we conducted a functional magnetic resonance imaging study using picture stimuli to induce negative (vs. neutral) affect and thermal stimuli to induce heat pain (vs. warmth perception). The painful heat stimuli were administrated at an individual temperature for each subject. Twenty patients with BPD and 23 healthy control subjects were included in the study. - Results - Both negative and neutral pictures led to stronger activation of the amygdala, insula, and anterior cingulate cortex in patients with BPD than in healthy control subjects. Amygdala activation correlated with self-reported deficits in emotion regulation. During the sensory stimulation, we found decreased amygdala and anterior cingulate cortex activation, which was independent of painfulness. - Conclusions - The results are in line with previous findings on emotional hyperactivity in BPD and suggest that pain stimuli in BPD are processed differently depending on the arousal status. Finally, we can preliminarily support the idea of a general mechanism of attentional shift underlying the soothing effect of pain in BPD.